A Defence of Lucretian Presentism. Issue 4 (1st October 2020) - Tallant, Jonathan; Ingram, David
ABSTRACT: In this paper, we defend Lucretian Presentism ('Lucretianism'). Although the view faces many objections and has proven unpopular with presentists, we rehabilitate Lucretianism and argue that none of the objections stick.